Enzymatic Activity of Actinomycetes Isolated from Marine Sedimentes - and A. M. Deshmukh2, R. M. Gulve1 (Recent Research in Science and Technology, 2011)
The marine environment represents a largely untapped source for isolation of new microorganisms. Gram positive actinomycete bacteria are of special interest, since they are known to produce chemically diverse compounds with a wide range of biological activities. Totally, 107 different actinomycetes were isolated from marine sediments, collected from five coastal sites of Konkan coast of Maharashtra.90 actinomycetal isolates were identified up to generic level. It was found that these actinomycetal isolates were belonging to Streptomyces, Micromonospora, Intrasporangium, Saccharopolyspora, Streptosporangium, Rhodococcus, Saccharomonospora and Nocardia. Enzymatic activities of 90 identified actinomycetal isolates were performed. It was found that out of 90 actinomycetes 76 (84.44 %), 70 (77.78%), 65 (72.22%), 39 (43.33%), 34 (37.78%) and 15 (16.67%) number of actinomycetes were possessing protease, gelatinase, amylase, lecithinase, cellulase and ureases activity respectively.